Self-advocacy for people with intellectual disability in Sweden – organizational similarities and differences - Mallander, Ove; Mineur, Therese; Henderson, David; Tideman, Magnus (Disability Studies Quarterly, 2018)
Self-determination and the ability to express opinions and preferences are fundamental to all people. Self-advocacy (SA) among people with intellectual disability (PWID) presents opportunities for them to develop skills to have a say and influence changes in their local environments. The aim of this article is to explore and understand organizational similarities and differences of SA groups for PWID in Sweden by focusing their structures and activities. Within the theoretical framework of Resource-Dependency and New Institutional Perspectives, data from six Swedish SA groups belonging to two different national organizations, have been analyzed. Factors such as affinity and expectations show limited differences, while power distribution, rules and the role of support persons point to greater diversity. However, good relations within the local organizational field seems to be essential to maintain strong SA for PWID.